Chile : Selected Issues. (IMF Staff Country Reports; Country Report, 2012)
The Selected Issues paper discusses external shocks and its effects on Chile. The economy of Chile is susceptible to global financial predicaments, external demands, and commodity rates. This paper reports on financial spillovers from 2008-12, its methodologies, and the pressures on bank funding markets. The paper also examines performance of nonfinancial sector during the 2008-09 crisis. The Executive Board sees the document as an analytical description of Chile in the global scene.